Mentoring Practices in English Language Teaching Practicum: Student Teachers' Perspectives on Cooperating Teachers' Roles in the Turkish Context. Issue 3 (2nd July 2020) - Aydın, Özge; Ok, Ahmet
Abstract: The present study aimed to investigate cooperating teachers' mentoring practices by focusing on student teachers' perspectives on the fulfillment of mentoring roles-responsibilities and reveal possible differences in these perspectives in relation to student teachers' gender, their willingness to teach, and their university. The participants were senior student teachers ( N = 205) enrolled in a Practice Teaching course in the Spring semester of 2016 at the English Language Teaching departments of two state universities in Turkey. A sixty-item instrument was utilized to collect quantitative data from student teachers. The data was analyzed through descriptive statistics and MANOVAs in the Statistical Package for Social Sciences. The findings showed student teachers' perceptions of the fulfillment of their mentors' roles-responsibilities ranging between "agree" and "tend to disagree". While the mentees' gender did not have a significant effect on their perceptions regarding the fulfillment of mentoring roles-responsibilities, their willingness to teach and university significantly influenced their perceptions.